Perceptual error in medical practice - Greig, P (2016)
Introduction Medical errors are major hazards, and lapses in non-technical skills such as situational awareness contribute to most incidents. Risks are concentrated in acute care, and in crisis situations clinicians can apparently ignore vital information. Poor workplace ergonomics contributes to risk. Existing work into perceptual errors offers insights, but these phenomena have been little researched in medicine. This thesis considers medical non-technical skills and how they are taught, and explores vulnerability to inattentional and change blindness.MethodsMedical human factors and the psychology of perceptual error were reviewed, and a mixed-methods assessment of postgraduate medical curricula completed.Experiments assessed clinicians’ interaction with clinical monitoring devices using eye-tracking, and studies were conducted exposing clinicians to various perceptual error stimuli using non-clinical and clinical videos, and simulation. A survey was also conducted to assess clinicians’ insight into the phenomena of perceptual error.ResultsNon-technical skills feature poorly in medical curricula, and equipment is poorly standardised in critical care areas. Unfamiliar devices slow response times and increase error rate.Clinical training confers no generalisable advantage in perceptual reliability. Even expert clinicians miss important events. Two out of every three life-support instructors for example missed a critical failure in the patient’s oxygen supply when watching a recorded emergency simulation.The insight and understanding healthcare staff have of perceptual errors is poor, leading to significant overestimates of perceptual reliability that could have consequences for clinical practice.ConclusionsPerceptual errors represent a latent risk factor contributing to loss of situational awareness. High rates of perceptual error were observed in the video-based experiment. Although lower rates were observed in simulation, important events were still missed by participants that could have serious consequences.The incidence of perceptual error appears sensitive to the method used to test for it, and this has important implications for the design of future experiments testing for these phenomena.Mitigating perceptual error is likely to be challenging, but relatively simple adjustments to team practices in emergency situations may be fruitful.